Clinical performance of 3d printed resin composite posterior fixed dental prosthesis a permanent solution - Hobbi, Paniz; Ordueri, Tuğçe Merve; Öztürk Bozkurt, Funda; Toz Akalın, Tuğba; Ateş, Mehmet Muzaffer; Özcan, Mutlu (My University, 2025)
Objectives: This clinical trial aimed to evaluate the clinical outcomes of 3D-printed resin composite posterior fixed dental prosthesis (FDP) restorations. Materials and Methods: Between October 2020 and August 2022, 49 patients (33 females, 16 males, aged 19-60) received 68 3-unit 3D-printed resin composite posterior FDPs (ELS Even Stronger, Saremco, Switzerland). Follow-ups were conducted at baseline (2 weeks) by independent observers using modified FDI criteria, assessing anatomical form, marginal adaptation, surface roughness, color match, fracture, retention, and patient feedback. Fifty FDPs completed a 1-year follow-up, and 18 reached 2 years. Results: The mean observation period was 14.15 months. Failures were categorized as mechanical or bio-logical, with 19 FDPs failing: 14 mechanical (12 cohesive fractures) and 5 biological (3 needing endodontic treatment, 2 periodontal issues). Two FDPs were recemented. Three FDPs showed surface luster loss, color mismatches, and staining. The survival rate based on mechanical failures was 69.5%, dropping to 61.0% when including biological com-plications. Conclusions: After 2 years, 3D-printed resin composite FDPs demonstrated acceptable performance, with most failures due to fractures in the connector region, suggesting the need for design revisions.
Keywords: Clinical Trial; Composite 3-Unit Posterior FDPs; Dental Materials; Prosthodontics; Restorative Materials; Survival